"At our age, we would like to do things the way we want: " a qualitative study of adolescent HIV testing services in Kenya. (1st July 2017) - Wilson, Kate S.; Beima-Sofie, Kristin M.; Moraa, Helen; Wagner, Anjuli D.; Mugo, Cyrus; Mutiti, Peter M.; Wamalwa, Dalton; Bukusi, David; John-Stewart, Grace C.; Slyker, Jennifer A.; Kohler, Pamela K.; O'Malley, Gabrielle
Abstract : Objectives: Adolescents in Africa have low HIV testing rates. Better understanding of adolescent, provider, and caregiver experiences in high-burden countries such as Kenya could improve adolescent HIV testing programs. Design: We conducted 16 qualitative interviews with HIV-positive and HIV-negative adolescents (13–18 years) and six focus group discussions with Healthcare workers (HCWs) and caregivers of adolescents in Nairobi, Kenya. Methods: Semi-structured interviews and focus groups were recorded and transcribed. Analysis employed a modified constant comparative approach to triangulate findings and identify themes influencing testing experiences and practices. Results: All groups identified that supportive interactions during testing were essential to the adolescent's positive testing experience. HCWs were a primary source of support during testing. HCWs who acted respectful and informed helped adolescents accept results, link to care, or return for repeat testing, whereas HCWs who acted dismissive or judgmental discouraged adolescent testing. Caregivers universally supported adolescent testing, including testing with the adolescent to demonstrate support. Caregivers relied on HCWs to inform and encourage adolescents. Although peers played less significant roles during testing, all groups agreed that school-based outreach could increase peer demand and counteract stigma. All groups recognized tensions around adolescent autonomy in the absence of clear consent guidelines. Adolescents valued support people during testing but wanted autonomy over testing and disclosure decisions. HCWs felt pressured to defer consent to caregivers. Caregivers wanted to know results regardless of adolescents' wishes. Conclusion: Findings indicate that strengthening HCW, caregiver, and peer capacities to support adolescents while respecting their autonomy may facilitate attaining '90-90-90' targets for adolescents. Abstract : Supplemental Digital Content is available in the text